1999
DOI: 10.1038/sj.bjp.0702366
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin II receptor blockade on proximal fluid uptake in the rat kidney

Abstract: 1 Angiotensin II has a well described dose-dependent biphasic action on proximal tubule¯uid uptake, although the concentration and eect of endogenous luminal angiotensin II remain controversial. 2 Shrinking split-droplet micropuncture was used to examine the¯uid uptake in response to the luminal application of three AT 1 antagonists (losartan, EXP3174, candesartan). 4 All three antagonists at a low concentration (10 78 M) decreased¯uid uptake. EXP3174 and candesartan at a higher concentration (10 75 M) also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(28 reference statements)
2
4
0
Order By: Relevance
“…However, the mechanisms by which hypertension contributes to the progression of renal injury is not clear. In this study, we observed that AngII exposure resulted in significant up-regulation of TNFα and IL-1β in NRK52E cells after 6 h. Our results are consistent with those of previous studies which have shown that AngII infusion increases the production of PIC in rat kidneys [53][54][55]. Although previous studies have investigated the effects of AngII on kidneys, the upstream signaling mechanism are not well understood.…”
Section: Discussionsupporting
confidence: 94%
“…However, the mechanisms by which hypertension contributes to the progression of renal injury is not clear. In this study, we observed that AngII exposure resulted in significant up-regulation of TNFα and IL-1β in NRK52E cells after 6 h. Our results are consistent with those of previous studies which have shown that AngII infusion increases the production of PIC in rat kidneys [53][54][55]. Although previous studies have investigated the effects of AngII on kidneys, the upstream signaling mechanism are not well understood.…”
Section: Discussionsupporting
confidence: 94%
“…17,18 In a previous study using in vivo spilt-droplet micropuncture, luminal injection of candesartan inhibited fluid transport by 20%. 19 The degree of reduction of proximal fluid transport by candesartan when estimated by lithium clearance was less than that reported using microperfusion, perhaps because changes in lithium clearance reflect effects in all proximal tubules rather than only in superficial nephrons. This interpretation is supported by a study using both intravenous injection and proximal microperfusion of the AngII receptor antagonist DuP753.…”
Section: Discussionmentioning
confidence: 81%
“…Inhibition of proximal fluid transport by intravenous infusion of candesartan may be mediated by blockade of receptors at either luminal or peritubular sites and AT 1 receptors have been reported on both luminal and basolateral membranes of proximal tubule cells 17,18 . In a previous study using in vivo spilt‐droplet micropuncture, luminal injection of candesartan inhibited fluid transport by 20% 19 . The degree of reduction of proximal fluid transport by candesartan when estimated by lithium clearance was less than that reported using microperfusion, perhaps because changes in lithium clearance reflect effects in all proximal tubules rather than only in superficial nephrons.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequently, cAMP activates protein kinase A, which phosphorylates various proteins including AQP2 and the type 1 bumetanidesensitive Na-K-2Cl cotransporter (NKCC2 ) (7,16,46). ANG II also stimulates aldosterone secretion and increases sodium and bicarbonate reabsorption in the kidney proximal tubule via AT 1 receptors (18,35,52,53). Several studies have demonstrated that ANG II also has an important effect on the TAL and collecting duct in addition to the proximal tubules (2,35).…”
mentioning
confidence: 97%